Teacher Perception Toward Selection and Recruitment of Civil Servant Teachers in Science Subjects in Lombok - Sri Trisnadewi; Nurfaradilla Mohamad Nasri (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2021)
Teacher quality is an important factor in determining the growth and development of a nation. Therefore, the process of selecting and recruiting Civil Servant teachers play an important role in ensuring in Indonesia. This study aims to explore the process employed in the select candidate for civil servant teachers in Indonesia and to discover teacher perceptions’ of the system. This study involved five (5) voluntary civil servant science teachers in Lombok, West Nusa Tenggara, Indonesia. The study design employs a case study with the Miles and Huberman model to analyze the data. An online interview approach was used to collect the data. The result indicates that all participants believed that the selection and recruitment system is transparent. In addition, the challenge in the form of an insufficient budget causes the issue of shortage of teaching staff in Indonesia to become an issue that is still valid today. What needs to be done to overcome this problem is that the government needs to increase the budget in the process of selecting and recruiting civil servant teachers in Indonesia.